Answer:
Rewriting [tex]6^{-2}[/tex] without an exponent we get [tex]\mathbf{\frac{1}{36}}[/tex]
Step-by-step explanation:
We need to rewrite the following without an exponent. [tex]6^{-2}[/tex]
We need to solve the exponent to find the result.
We know the exponent rule: [tex]a^{-b}=\frac{1}{a^b}[/tex]
Now using this rule to solve the equation:
[tex]6^{-2}\\=\frac{1}{6^2}\\We \:know \:that\:6^2 = 6\times 6=36\\=\frac{1}{36}[/tex]
So, Rewriting [tex]6^{-2}[/tex] without an exponent we get [tex]\mathbf{\frac{1}{36}}[/tex]